PENYULUHAN ADMINISTRASI DAN PELAPORAN PAJAK SEDERHANA BAGI WAJIB PAJAK PELAKU USAHA KECIL DI KELURAHAN KEDAUNG KALI ANGKE, KOTA JAKARTA BARAT - Radita Arindya; Didi Sukardi; Rahmatullah Rahmatullah; I Nyoman Suri Adnyana; Dewi Sulistyani; Murdiyono Murdiyono (Nusantara Hasana Journal, 2023)
This community service activity aims to improve small business owners' understanding of tax administration and simple tax reporting in Kedaung Kali Angke Village, West Jakarta City. The main problem faced by participants was a lack of knowledge regarding simple and correct business registration procedures, tax calculations, and Tax Return (SPT) reporting. The activity was implemented through lectures and Q&A discussions involving small business owners as the main participants. The material provided covered the importance of tax compliance, simple business administration, procedures for calculating MSME taxes, and the use of digital tax services. The results of the activity showed that participants gained a better understanding of tax obligations and the importance of orderly business records. This activity is expected to increase tax awareness and compliance among small business owners, thereby supporting increased state revenue and the development of more orderly business administration.